Method and system for auxiliary recovery of waste lithium battery negative electrode material by using transition metal burning reducer
By using ferrous sulfide as a transition metal burn-down reducer, the heat treatment temperature of waste graphite of lithium battery negative electrode material is reduced, the problem of high temperature cost is solved, and efficient and economical graphite regeneration is achieved.
Patent Information
- Application Number
- CN202510193433.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-21
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2045-02-21
AI Technical Summary
The recycling of waste graphite of lithium battery negative electrode material requires high temperature heat treatment, resulting in high cost and limited value.
Ferrous sulfide is used as the transition metal descaling agent, and the temperature of the graphite heat treatment to restore the crystal structure is reduced by mixing it with acid-impregnated graphite and heating it at 700°C to 780°C.
It effectively reduces the energy consumption and cost of recycled graphite, improves the economic value of graphite, and makes recycled graphite have a good crystal structure.
Smart Images

Figure CN119674306A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery materials, and in particular relates to a method and system for recovering negative electrode materials of waste lithium batteries with the assistance of a transition metal burning reducer. Background Art
[0002] In similar experimental schemes for heat treatment of acid-leached graphite, the main point is that researchers often use a transition metal salt to assist in the recovery of the crystal structure of waste graphite. For example, some researchers reduced the heat treatment temperature to 800°C and restored the graphite structure to a certain extent by mixing acid-leached graphite with ferric chloride and combining it with the effect of glucose; some researchers reduced the heat treatment temperature to 900°C by using cobalt nitrate, and restored the graphite after heat treatment to a good crystal structure. The addition of transition metal salts keeps the carbon atoms in the graphite active through the redox trend of transition metal ions, thereby reducing the temperature required to restore the crystal structure.
[0003] The recycling of waste graphite for lithium negative electrode materials generally requires several major steps: lithium battery discharge-crushing-positive and negative electrode material powder sorting-negative electrode material acid leaching-heat treatment. Among them, the heat treatment stage is of great significance for removing excess binder, releasing structural electrolyte and restoring graphite structure, especially for recycling waste graphite for the preparation of lithium-ion battery negative electrodes. However, the heat temperature here is generally between 1500 and 3000 ° C, which limits the value of graphite recycling in terms of heat treatment costs. Relevant researchers have proposed the use of transition metal compounds such as ferric chloride and cobalt nitrate to assist in heat treatment to reduce the heat treatment temperature to about 900 to 1000 ° C. Based on this principle, the present invention further improves heat treatment to reduce burning.
[0004] Through the above analysis, the problems and defects of the prior art are as follows: The recycling of waste graphite from lithium negative electrode materials generally requires several major steps: lithium battery discharge - crushing - positive and negative electrode material powder sorting - negative electrode material acid leaching - heat treatment. The heat temperature is generally between 1500 and 3000 ° C. In terms of heat treatment costs, the value of graphite recycling is limited. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention provides a method for recovering negative electrode materials of waste lithium batteries using a transition metal burning reducer as an aid.
[0006] The present invention is achieved by: a method for recovering waste lithium battery negative electrode materials with the aid of a transition metal burning reducing agent, comprising: Step 1: Mix the negative electrode black powder with concentrated sulfuric acid and stir at 50°C~100°C for 3~5h.
[0007] Step 2: After filtering, deionized water is added to the leached solid to adjust it to neutrality, and then heated at 50° C. to 100° C. for more than 10 h to 15 h to obtain acid-leached graphite.
[0008] Step 3, mixing ferrous sulfide powder with ethanol or deionized water to obtain a ferrous sulfide solution, adding the ferrous sulfide solution dropwise to the acid-leached graphite at a mass ratio of 1:0.1-0.5 and continuously stirring for 1-3 hours.
[0009] Step 4, heating the obtained mixture at 700° C. to 780° C. for 10 h to 15 h under a nitrogen flow to obtain a heat-treated solid.
[0010] Step 5, after the solid is cooled, it is washed with hydrochloric acid, and the obtained filter residue is adjusted to neutral with deionized water, and then heated in an oven at 50°C to 100°C for more than 10h to 15h to obtain regenerated graphite.
[0011] Step 6: The filtrate obtained after washing with hydrochloric acid can be precipitated by adding a reducing agent to obtain elemental iron, or can be used as a ferric chloride solution to continue to participate in the heat treatment of waste graphite to reduce burning.
[0012] Furthermore, the acid leaching with sulfuric acid mainly removes single elements such as copper, aluminum, iron, and lithium.
[0013] Furthermore, the transition metal salt ferrous sulfide promotes the reconstruction of the graphite crystal structure.
[0014] Furthermore, the hydrochloric acid is washed to remove compounds such as ferrous chloride and ferrous sulfide, and heated to remove water and excess hydrochloric acid.
[0015] Another object of the present invention is to provide a system for recovering waste lithium battery negative electrode materials by using a transition metal burning reducing agent, comprising: The mixing module is used to mix the negative electrode black powder with concentrated sulfuric acid and stir at 50°C~100°C for 3~5h.
[0016] The regulating module is used to add deionized water to the leached solids after filtration to adjust them to neutrality, and heat them at 50°C~100°C for more than 10h~15h to obtain acid-leached graphite.
[0017] The stirring module is used to mix ferrous sulfide powder with ethanol or deionized water to obtain a ferrous sulfide solution, and the ferrous sulfide solution is added dropwise to the acid-leached graphite at a mass ratio of 1:0.1~0.5 and continuously stirred for 1~3 hours.
[0018] The heating module is used to heat the obtained mixture at 700° C. to 780° C. for 10 h to 15 h under a nitrogen flow to obtain a heat-treated solid.
[0019] The cleaning module is used to clean the solid with hydrochloric acid after it is cooled. The obtained filter residue is adjusted to neutral with deionized water and then heated in an oven at 50°C to 100°C for more than 10h to 15h to obtain regenerated graphite.
[0020] The heat treatment module is used to obtain the filtrate after hydrochloric acid washing by adding a reducing agent to precipitate the iron element, or to continue to participate in the heat treatment of waste graphite as a ferric chloride solution to reduce the burning.
[0021] In combination with the above technical solutions and the technical problems solved, the advantages and positive effects of the technical solutions to be protected by the present invention are as follows: First, the present invention proposes ferrous sulfide (FeS) as a graphite activator to reduce the temperature required for waste graphite to restore its crystal structure by heating during heat treatment to 750°C, thereby further reducing the energy consumption and cost required for regenerating graphite and expanding the economic space for regenerating graphite.
[0022] The present invention designs a method for recovering waste lithium battery negative electrode materials with the assistance of a transition metal burning reduction agent. After the acid leaching process, the transition metal salt ferrous sulfide is mixed with the acid-leached graphite for heat treatment, and the reaction activity of the graphite material is enhanced by the ferrous sulfide, thereby reducing the temperature required for the recovery of the crystal structure of the waste graphite during heat treatment. The selected transition metal salt ferrous sulfide has a low cost. On the basis of existing research, the ferrous sulfide we use further reduces the sintering temperature to 750°C and makes the regenerated graphite have a good crystal structure. The filtrate from which the sulfur and iron elements are removed can be reused to regenerate iron metal and can also be reused to reduce burning. The entire experimental process is relatively simple and the experimental repeatability is strong.
[0023] The invention designs a method for recovering waste lithium battery negative electrode materials with the aid of a transition metal burning reduction agent, and provides a new method for the regeneration of waste graphite.
[0024] As described in the background above, the prior art solution is based on the principle that transition metal salts can increase the activity of carbon atoms in graphite. The present invention designs a method for recovering waste lithium battery negative electrode materials with the assistance of a transition metal burning reducer. By mixing a transition metal salt ferrous sulfide solution with acid-leached graphite for heat treatment after the acid leaching process, the reaction activity of the graphite material is enhanced by ferrous sulfide, thereby reducing the temperature required for the recovery of the crystal structure of the waste graphite during heat treatment. The selected transition metal salt ferrous sulfide has a low cost. Based on existing research, the ferrous sulfide we use further reduces the sintering temperature to 750°C and makes the regenerated graphite have a good crystal structure. The filtrate from which sulfur and iron elements are removed can be reused to regenerate iron metal and can also be reused to reduce burning. The entire experimental process is relatively simple and the experimental repeatability is strong.
[0025] Second, the expected benefits and commercial value of the technical solution of the present invention after transformation are as follows: the present invention mainly uses transition metal salt calcination reducing agent to reduce the sintering temperature of lithium battery negative electrode materials in the recycling process, thereby reducing the cost required for the recycling of lithium negative electrode materials. The lattice structure of the lithium negative electrode material obtained by sintering is relatively complete and can be used again as the preparation of lithium battery negative electrode. In general, this method broadens the economic benefit space of lithium battery recycling. Considering the increasing number of discarded batteries in the existing market environment, this solution has certain commercial value. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a flow chart of a method for recovering negative electrode materials of waste lithium batteries using a transition metal burning reducer assisted by an embodiment of the present invention.
[0027] Figure 2 This is a system structure diagram of the transition metal burning reducer assisted recovery of waste lithium battery negative electrode materials provided by an embodiment of the present invention.
[0028] Figure 3 It is a detailed flow chart of the method for recovering negative electrode materials of waste lithium batteries using a transition metal burning reducer assisted by an embodiment of the present invention. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0030] like Figure 1 As shown, a method for recovering waste lithium battery negative electrode materials with the aid of a transition metal burning reducing agent provided in an embodiment of the present invention comprises the following steps: S101, mix the negative electrode black powder with concentrated sulfuric acid and stir at 50℃~100℃ for 3~5h.
[0031] S102, after filtering, adding deionized water to the leached solid to adjust to neutrality, and heating at 50°C to 100°C for more than 10h to 15h to obtain acid-leached graphite.
[0032] S103, mixing ferrous sulfide powder with ethanol or deionized water to obtain a ferrous sulfide solution, adding the ferrous sulfide solution dropwise to the acid-leached graphite at a mass ratio of 1:0.1-0.5 and continuously stirring for 1-3 hours.
[0033] S104, heating the obtained mixture at 700° C. to 780° C. for 10 h to 15 h under a nitrogen flow to obtain a heat-treated solid.
[0034] S105, after the solid is cooled, it is washed with hydrochloric acid, and the obtained filter residue is adjusted to neutral with deionized water, and then heated in an oven at 50°C to 100°C for more than 10h to 15h to obtain regenerated graphite.
[0035] S106, the filtrate obtained after washing with hydrochloric acid can be precipitated by adding a reducing agent to obtain elemental iron, or can be used as a ferric chloride solution to continue to participate in the heat treatment of waste graphite to reduce burning.
[0036] In step S101, the negative electrode black powder of the waste lithium battery is mixed with concentrated sulfuric acid and stirred at 50°C to 100°C for 3 to 5 hours to dissolve the metal impurities (such as lithium salts, aluminum foil, etc.) in the black powder. The strong acidic environment of concentrated sulfuric acid oxidizes and dissolves the impurities into soluble sulfates, further removing non-graphite materials and laying the foundation for subsequent purification.
[0037] In step S102, after acid leaching, the leachate and solid residue are separated by filtration, and deionized water is added to the leached solid to adjust it to neutrality, and heated at 50°C to 100°C for 12 hours. This process can further clean the residual impurities on the surface of the graphite particles, promote the precipitation of impurities in the solution, ensure the purity of the acid-leached graphite, and prepare for the subsequent de-burning treatment.
[0038] In step S103, ferrous sulfide powder is mixed with ethanol or deionized water to form a ferrous sulfide solution, which is then added dropwise to the acid-leached graphite at a mass ratio of 1:0.1-0.5 and stirred continuously. Ferrous sulfide, as a transition metal calcination reducing agent, reacts with the graphite interface to form a protective film of iron sulfide, which enhances the structural stability of the graphite particles and prevents the graphite from further decomposition or oxidation during high temperature treatment.
[0039] In step S104, the mixture is placed in a nitrogen flow and heated at 700°C to 780°C for 12 hours. Under high temperature conditions, ferrous sulfide reacts chemically with impurities on the surface of graphite, and the impurities are reduced, oxidized or volatilized, thereby further purifying the graphite. In addition, the presence of ferrous sulfide can significantly reduce the burning rate of graphite, protect the graphite structure, and make it have properties close to those of native graphite.
[0040] In step S105, the solid obtained after the heat treatment is washed with hydrochloric acid to remove soluble impurities formed during the heat treatment. The washed filter residue is adjusted to neutrality with deionized water, and then dried in an oven at 50°C to 100°C for 12 hours to finally obtain regenerated graphite. The regenerated graphite has a complete structure, excellent conductivity and high temperature resistance, and can be recycled as a negative electrode material for lithium batteries.
[0041] In step S106, the filtrate after washing with hydrochloric acid contains iron ions, and the iron can be recovered by adding a reducing agent (such as hydrogen or ferrous sulfate) for precipitation. If the iron is not recovered, the filtrate is used as a ferric chloride solution to continue to participate in the subsequent heat treatment process of waste graphite, and is recycled to further improve resource utilization efficiency, reduce waste liquid discharge, and reduce environmental burden.
[0042] Through a multi-step process of acid leaching, neutralization, ferrous sulfide treatment, high-temperature heat treatment, hydrochloric acid cleaning and resource utilization, this method can maximally purify waste graphite while significantly reducing the graphite burnout rate, and realize material recycling through the recovery of by-products, which is both efficient and environmentally friendly.
[0043] The acid leaching of sulfuric acid provided in the embodiment of the present invention mainly removes single elements such as copper, aluminum, iron, and lithium.
[0044] The transition metal salt ferrous sulfide provided by the embodiment of the present invention promotes the reconstruction of the graphite crystal structure.
[0045] The hydrochloric acid cleaning provided in the embodiment of the present invention is used to remove compounds such as ferrous chloride and ferrous sulfide, and heating is used to remove water and excess hydrochloric acid.
[0046] like Figure 2 As shown, a system for recovering waste lithium battery negative electrode materials with the aid of a transition metal burning reduction agent provided in an embodiment of the present invention comprises: The mixing module is used to mix the negative electrode black powder with concentrated sulfuric acid and stir at 80°C for 3 to 5 hours.
[0047] The regulating module is used to add deionized water to the leached solids after filtration to adjust them to neutrality, and heat them at 80°C for more than 12 hours to obtain acid-leached graphite.
[0048] The stirring module is used to mix ferrous sulfide powder with ethanol or deionized water to obtain a ferrous sulfide solution, and the ferrous sulfide solution is added dropwise to the acid-leached graphite at a mass ratio of 1:0.1~0.5 and continuously stirred for 1~3 hours.
[0049] The heating module is used to heat the obtained mixture at 750° C. for 12 hours under a nitrogen flow to obtain a heat-treated solid.
[0050] The cleaning module is used to clean the solid with hydrochloric acid after it is cooled. The obtained filter residue is adjusted to neutral with deionized water and then heated in an oven at 80°C for more than 12 hours to obtain regenerated graphite.
[0051] The heat treatment module is used to obtain the filtrate after hydrochloric acid washing by adding a reducing agent to precipitate the iron element, or to continue to participate in the heat treatment of waste graphite as a ferric chloride solution to reduce the burning.
[0052] The present invention is specifically implemented: Experimental process: Set up one experimental sample and two control samples. The specific implementation process is as follows: Figure 1 and supplemented with text.
[0053] Experimental sample 1: like Figure 3 As shown, the processing starts directly from the negative electrode material powder. The initial process is roughly as follows: Recycle used batteries - Let them stand in a 1 mol / L NaCl solution for more than 24 hours to fully discharge - Use a machine to crush and grind the batteries into powder - Use an airflow separation process to separate the positive and negative electrode black powders.
[0054] 1. Mix the negative electrode black powder with concentrated sulfuric acid and stir at 80°C for 3 to 5 hours (at this time, sulfuric acid leaching mainly removes single elements such as copper, aluminum, iron, and lithium).
[0055] 2. After filtering, add deionized water to the leached solid to adjust it to neutrality, and heat it at 80°C for more than 12 hours to obtain acid-leached graphite.
[0056] 3. Mix ferrous sulfide powder with ethanol or deionized water to obtain a ferrous sulfide solution, add the ferrous sulfide solution to the acid-leached graphite at a mass ratio of 1:0.1~0.5 and continue stirring for 1~3h (to fully mix the ferrous sulfide and graphite).
[0057] 4. The obtained mixture was heated at 750° C. for 12 h under nitrogen flow to obtain a heat-treated solid (the reconstruction of the graphite crystal structure was promoted by the transition metal salt ferrous sulfide).
[0058] 5. After the solid is cooled, it is washed with hydrochloric acid. The resulting filter residue is adjusted to neutral with deionized water and heated in an oven at 80°C for more than 12 hours to obtain regenerated graphite (washed with hydrochloric acid to remove compounds such as ferrous chloride and ferrous sulfide, and heated to remove water and excess hydrochloric acid).
[0059] 6. The filtrate obtained after washing with hydrochloric acid can be precipitated by adding a reducing agent to obtain elemental iron, or it can be used as a ferric chloride solution to continue to participate in the heat treatment of waste graphite to reduce burning.
[0060] Control sample 1 (acid-leached graphite): 1. Mix the negative electrode material powder with concentrated sulfuric acid and stir at 80℃ for 3~5h. To maintain consistency, the negative electrode black powder needs to be kept at 700℃ for 2h before use to remove the residual binder.
[0061] 2. After filtering, add deionized water to the leached solids to adjust to neutrality.
[0062] 3. Heat the acid-impregnated graphite in an oven at 80°C for more than 12 hours to obtain control sample 1 (acid-impregnated graphite).
[0063] Control sample 2 (based on control sample 1 acid-leached graphite): 1. Mix the negative electrode material powder with concentrated sulfuric acid and stir at 80°C for 3-5 hours. Here, the negative electrode material powder needs to be kept at 700°C for 2 hours to remove the residual binder.
[0064] 2. After filtering, add deionized water to the leached solids to adjust to neutrality to obtain acid-leached graphite.
[0065] 3. Heat the acid-impregnated graphite in an oven at 80°C for 12 hours to obtain a control sample powder.
[0066] 4. Dissolve the control sample 1 powder and ferrous chloride tetrahydrate in ethanol at a mass ratio of 1:0.1~0.5, and continue stirring for 1~3h (the relative content of iron element remains consistent with that of the experimental group).
[0067] 5. The obtained mixture was heated at 900°C for 12 hours under nitrogen flow to obtain a heat-treated solid. After the solid was cooled, it was washed with hydrochloric acid, and the obtained residue was adjusted to neutral with deionized water and heated in an oven at 80°C for more than 12 hours to obtain regenerated graphite.
[0068] Table 1 Main chemical composition of each group of graphite
[0069] As can be seen from Table 1, in terms of elemental composition, the control group 1 (acid-leached graphite) contains more impurities such as aluminum and iron, and even a small amount of lithium has not been removed. At the same time, compared with the control group 2, the experimental group has a higher carbon mass ratio and a lower impurity content, and the impurity removal levels of the two are roughly at the same level.
[0070] Table 2 Main physical properties of graphite in each group
[0071] Comparing the physical parameters in Table 2, it can be seen that the mean particle size, specific surface area and average pore size of the control group 1 (acid-leached graphite) are quite different from those of the control group 2 and the experimental group. This is mainly because the heat treatment process can reduce the alkaline groups on the graphite surface, fill vacancy defects, etc., thereby effectively restoring the crystal structure of the graphite. Further comparison found that the physical property parameters of the control group 2 and the experimental group were not much different, and the values were basically at the same level. Therefore, based on the fact that the crystal structure recovery level of the graphite after both treatments is roughly the same, the ferrous sulfide solution shows better heat treatment and burning reduction performance, so that the waste graphite can achieve the recovery of the crystal structure at a lower temperature. The cost of recycling and reusing waste graphite is further reduced, especially the heat-treated graphite can be used again as a negative electrode material for lithium-ion batteries, thereby realizing the recycling of lithium battery materials.
[0072] Key points: 1. The core point is to enhance the activity of carbon atoms in graphite by uniformly mixing ferrous sulfide solution with acid-impregnated graphite so as to reduce the temperature required for lattice structure recovery (that is, when the lattice structure recovery level is roughly the same, the heat treatment temperature is further reduced to reduce energy consumption).
[0073] 2. After washing the heat-treated graphite with hydrochloric acid, the resulting filtrate includes ferrous chloride and ferrous sulfide, etc., which can be either added with a reducing agent to obtain elemental iron or reused to perform heat treatment on the acid-leached graphite again.
[0074] 3. In the transition metal salt-graphite stage, the solution is first prepared and then added dropwise, accompanied by continuous stirring, so that the mixture at this stage is more uniform, which is conducive to the role of ferrous sulfide between graphites.
[0075] Among them, the areas that can be expanded are: 1. The selected calcination-reducing transition metal salts include ferrous sulfide, cobalt sulfide, nickel sulfide, and ferrous phosphate.
[0076] 2. The burning reducing agent is a mixed solution of transition metal salt and deionized water or ethanol.
[0077] 3. The impurity content of the regenerated graphite after heat treatment is low, with Al, Cu and Fe all below 50ppm, and it can be used as the negative electrode material of lithium secondary batteries.
[0078] 4. Negative electrode black powder can come from lithium iron phosphate, lithium cobalt oxide, lithium titanate, ternary and other lithium batteries.
[0079] 5. The concentration of sulfuric acid and hydrochloric acid used is 1~3 mol / L.
[0080] As described in the background above, the prior art solution is based on the principle that transition metal salts can increase the activity of carbon atoms in graphite. The present invention designs a method for recovering waste lithium battery negative electrode materials with the aid of a transition metal de-burning agent. After the acid leaching process, a transition metal salt ferrous sulfide solution is mixed with acid-leached graphite for heat treatment, and the reaction activity of the graphite material is enhanced by ferrous sulfide, thereby reducing the temperature required for the recovery of the crystal structure of the waste graphite during heat treatment.
[0081] Advantages: The selected transition metal salt ferrous sulfide has a low cost. Based on existing research, the ferrous sulfide we use further reduces the sintering temperature to 750°C and makes the regenerated graphite have a good crystal structure. The filtrate after removing sulfur and iron elements can be reused to regenerate iron metal and can also be reused to reduce sintering. The entire experimental process is relatively simple and the experiment is highly repeatable.
[0082] Lithium battery recycling: After thousands of charge and discharge cycles, lithium batteries reach their cycle life limit, performance degrades and become scrapped. At this time, for environmental and resource considerations, some of the internal resources are recycled and reused.
[0083] Graphite negative electrode material: Graphite is the main negative electrode material in commercial lithium-powered batteries and lithium batteries.
[0084] Discharging lithium batteries: Recycled lithium batteries may still have power inside. The first step in recycling is to completely discharge the battery, usually by soaking it in a NaCl solution.
[0085] Crushing and sorting: The lithium battery is directly crushed by physical means, and then the powder is obtained through drying, screening and other steps, and then air flow sorting is performed to obtain the positive electrode black powder and negative electrode black powder to be processed. The means here vary according to the specific method, and the negative electrode black powder here often contains more impurities, such as binders, lithium, iron, copper, aluminum, and even a small amount of positive electrode elements such as nickel, cobalt, and manganese.
[0086] Acid leaching: impurities in the negative electrode black powder are removed by mixing with high-concentration acid, thereby purifying the graphite to obtain acid-leached graphite.
[0087] Heat treatment: remove the solvent (deionized water, ethanol or acid), the focus is to restore the crystal structure of graphite to meet the needs of electrochemical performance of lithium-ion battery negative electrode materials, here the required temperature is relatively high, usually 1500~3000℃.
[0088] Example 1: Conventional recycling process for waste lithium battery negative electrode materials Objective: To efficiently extract recycled graphite from waste lithium battery negative electrode materials while recovering iron.
[0089] 1. Acid leaching purification: Take 10g of waste lithium battery negative electrode black powder, add 50mL of concentrated sulfuric acid (mass fraction 98%), and stir at 80℃ for 4 hours. In this process, the metal impurities (such as lithium, aluminum, etc.) in the negative electrode material are dissolved into soluble sulfates.
[0090] 2. Neutralization and cleaning: After filtration, the solid is adjusted to neutrality (pH about 7) with deionized water and heated at 80°C for 12 hours to remove residual acidic substances and attached impurities to obtain preliminarily purified acid-leached graphite.
[0091] 3. Ferrous sulfide treatment: Mix 2 g of ferrous sulfide powder with 50 mL of ethanol to make a ferrous sulfide solution, add it dropwise into the acid-leached graphite at a mass ratio of 1:0.2, and continue stirring for 2 hours to ensure that the ferrous sulfide is evenly coated on the surface of the graphite particles.
[0092] 4. High temperature heat treatment: The above mixture is placed in a nitrogen atmosphere and heated at 750°C for 12 hours to react the ferrous sulfide and remove residual impurities on the graphite surface while protecting the graphite structure.
[0093] 5. Hydrochloric acid washing: After cooling, the obtained solid was washed with 1M hydrochloric acid solution to remove soluble impurities and reaction by-products, then washed with deionized water to neutrality and dried at 80°C for 12 hours to obtain regenerated graphite.
[0094] 6. Recovery of iron: Add excess ferrous sulfate solution to the filtrate washed with hydrochloric acid for reduction to obtain iron precipitate, which is then further filtered and dried for recovery.
[0095] The purity of recycled graphite reaches over 98%, and its performance is close to that of original graphite. It can be used for recycling of negative electrode materials for lithium batteries.
[0096] The yield of recovered iron is 80%, and the by-products are recycled as resources.
[0097] Example 2: Modification and recovery process for enhancing high temperature resistance of graphite Graphite is purified through a multi-step process, and ferrous sulfide is used to protect the structure and modify the performance of graphite, further improving its high temperature resistance.
[0098] 1. Acid leaching purification: Take 20g of waste lithium battery negative electrode black powder, add 100mL of concentrated sulfuric acid, stir at 80℃ for 5 hours to dissolve metal impurities.
[0099] 2. Neutralization and cleaning: The acid-leached solid is repeatedly washed with deionized water until it is neutral, and heated at 80°C for 12 hours to obtain acid-leached graphite.
[0100] 3. Ferrous sulfide treatment: Mix 3g of ferrous sulfide powder with 100mL of deionized water to prepare a ferrous sulfide solution, add it dropwise to the acid-leached graphite at a mass ratio of 1:0.3, and continue stirring for 3 hours to allow the ferrous sulfide to fully coat the graphite surface.
[0101] 4. High temperature heat treatment: The mixture is placed in a nitrogen atmosphere and heated at 800°C for 12 hours to further remove impurities and improve the high temperature resistance of graphite through ferrous sulfide reaction.
[0102] 5. Hydrochloric acid cleaning and drying: After cooling, clean with 2M hydrochloric acid solution, remove by-products and adjust to neutral with deionized water, and dry at 80°C for 12 hours to obtain regenerated graphite with modified high temperature resistance.
[0103] 6. Recycling of filtrate: The cleaned filtrate is used as ferric chloride solution and recycled for the treatment of the next batch of waste graphite to improve resource utilization.
[0104] The high temperature resistance of recycled graphite is improved by 20%, and its structural stability and conductivity are significantly enhanced, so it can be directly used as high-performance lithium battery negative electrode materials.
[0105] The filtrate can be recycled, which reduces waste liquid discharge and reduces treatment costs.
[0106] These two examples respectively demonstrate the methods of optimizing the purification and performance modification of recycled graphite through different process conditions, while emphasizing the recycling of resources to achieve an efficient and environmentally friendly process route.
[0107] It should be noted that the embodiments of the present invention can be implemented by hardware, software, or a combination of software and hardware. The hardware part can be implemented using dedicated logic; the software part can be stored in a memory and executed by an appropriate instruction execution system, such as a microprocessor or dedicated design hardware. It can be understood by a person of ordinary skill in the art that the above-mentioned devices and methods can be implemented using computer executable instructions and / or contained in a processor control code, such as a carrier medium such as a disk, CD or DVD-ROM, a programmable memory such as a read-only memory (firmware), or a data carrier such as an optical or electronic signal carrier. Such code is provided on the carrier medium. The device and its modules of the present invention can be implemented by hardware circuits such as very large-scale integrated circuits or gate arrays, semiconductors such as logic chips, transistors, etc., or programmable hardware devices such as field programmable gate arrays, programmable logic devices, etc., can also be implemented by software executed by various types of processors, and can also be implemented by a combination of the above-mentioned hardware circuits and software, such as firmware.
[0108] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with the technical field within the technical scope disclosed by the present invention and within the spirit and principle of the present invention should be covered by the protection scope of the present invention.
Claims
1. A method for recovering waste lithium battery negative electrode materials using a transition metal burning reducing agent, characterized in that: The following steps are involved: Step 1, mixing the negative electrode black powder with concentrated sulfuric acid, and stirring at 50°C to 100°C for 3 to 5 hours; Step 2, after filtering, adding deionized water to the leached solid to adjust to neutrality, and heating at 50° C. to 100° C. for more than 10 h to 15 h to obtain acid-leached graphite; Step 3, mixing ferrous sulfide powder with ethanol or deionized water to obtain a ferrous sulfide solution, adding the ferrous sulfide solution dropwise to the acid-leached graphite at a mass ratio of 1:0.1-0.5 and continuously stirring for 1-3 hours; Step 4, heating the obtained mixture at 700° C. to 780° C. for 10 h to 15 h under a nitrogen flow to obtain a heat-treated solid; Step 5, after the solid is cooled, it is washed with hydrochloric acid, and the obtained filter residue is adjusted to neutral with deionized water, and then heated in an oven at 50°C to 100°C for more than 10h to 15h to obtain regenerated graphite; Step 6: The filtrate obtained after washing with hydrochloric acid can be precipitated by adding a reducing agent to obtain elemental iron, or can be used as a ferric chloride solution to continue to participate in the heat treatment of waste graphite to reduce burning.
2. The method for recovering waste lithium battery negative electrode materials using a transition metal burning reducing agent as claimed in claim 1, characterized in that: The acid leaching with sulfuric acid mainly removes single elements such as copper, aluminum, iron, and lithium.
3. The method for recovering waste lithium battery negative electrode materials using a transition metal burning reducing agent as claimed in claim 1, characterized in that: The transition metal salt ferrous sulfide promotes the reconstruction of the graphite crystal structure.
4. The method for recovering waste lithium battery negative electrode materials using a transition metal burning reducing agent as claimed in claim 1, characterized in that: The hydrochloric acid cleaning is used to remove compounds such as ferrous chloride and ferrous sulfide, and the heating is used to remove water and excess hydrochloric acid.
5. A system for recovering negative electrode materials of waste lithium batteries using a transition metal burning reducing agent, which implements the method for recovering negative electrode materials of waste lithium batteries using a transition metal burning reducing agent as claimed in any one of claims 1 to 4, characterized in that: The system for recovering waste lithium battery negative electrode materials with the aid of a transition metal burning reducing agent comprises: A mixing module is used to mix the negative electrode black powder with concentrated sulfuric acid and stir at 50°C to 100°C for 3 to 5 hours; A regulating module is used to add deionized water to the leached solids after filtering to adjust them to neutrality, and heat them at 50°C to 100°C for more than 10h to 15h to obtain acid-leached graphite; A stirring module is used to mix ferrous sulfide powder with ethanol or deionized water to obtain a ferrous sulfide solution, and the ferrous sulfide solution is added dropwise to the acid-leached graphite at a mass ratio of 1:0.1-0.5 and stirred continuously for 1-3 hours; A heating module is used to heat the obtained mixture at 700° C. to 780° C. for 10 h to 15 h under a nitrogen flow to obtain a heat-treated solid; The cleaning module is used to clean the solid with hydrochloric acid after cooling. The obtained filter residue is adjusted to neutral with deionized water and then heated in an oven at 50°C to 100°C for more than 10h to 15h to obtain regenerated graphite; The heat treatment module is used to obtain the filtrate after hydrochloric acid washing by adding a reducing agent to precipitate the iron element, or to continue to participate in the heat treatment of waste graphite as a ferric chloride solution to reduce the burning.
6. A method for recovering waste lithium battery negative electrode materials using a transition metal burning reducing agent, characterized in that: The following steps are involved: S101: Mix the negative electrode black powder of the waste lithium battery with concentrated sulfuric acid, and stir for 3 to 5 hours at 50°C to 100°C to dissolve the metal impurities; S102: After filtering, deionized water is added to the leached solid to adjust it to neutrality, and heated at 50° C. to 100° C. for more than 12 hours to obtain acid-leached graphite; S103: mixing ferrous sulfide powder with ethanol or deionized water to prepare a ferrous sulfide solution, adding the solution dropwise to the acid-leached graphite at a mass ratio of 1:0.1-0.5, and stirring for 1-3 hours; S104: heating the obtained mixture at 700° C. to 780° C. for 12 hours in a nitrogen atmosphere to obtain a heat-treated solid; S105: After the heat-treated solid is cooled, it is washed with hydrochloric acid, and the resulting filter residue is adjusted to neutral with deionized water and then dried at 50° C. to 100° C. for more than 12 hours to obtain regenerated graphite; S106: The filtrate obtained after washing with hydrochloric acid is precipitated by adding a reducing agent to obtain elemental iron, or is circulated as a ferric chloride solution to participate in the subsequent heat treatment process of waste graphite.
7. The method according to claim 6, characterized in that The mass fraction of the concentrated sulfuric acid in step S101 is 95% to 98%, and the stirring time is 4 hours.
8. The method according to claim 6, characterized in that The ferrous sulfide solution in step S103 is prepared by mixing ferrous sulfide powder and ethanol in a mass ratio of 1:10, and the stirring time is 2 hours.
9. The method according to claim 6, characterized in that In step S106, the filtrate after washing with hydrochloric acid is precipitated with iron by adding ferrous sulfate solution as a reducing agent, wherein the recovery rate of iron reaches more than 80%.
Citation Information
Patent Citations
Graphite and transitional metallic oxide composite cathode material and preparation method thereof
CN102903898A
Recycling and reusing method of waste lithium ion power battery anode materials
CN105552469A
Method for recycling waste lithium iron phosphate positive electrode material and applying recycled waste lithium iron phosphate positive electrode material to nickel-iron battery
CN106992328A
Method for recycling lithium iron phosphate positive electrode material in waste lithium ion battery
CN106992329A
Mixed transition metal borate negative electrode material and preparation method thereof
CN108023079A